Antitumor activity of the synthetic retinoid ST1926 on primary effusion lymphoma in vitro and in vivo models - Karam, Louna; Houshaymi, Bilal; Abdel-Samad, Rana; Jaafar, Mariam; Halloum, Iman; Pisano, Claudio; Neipel, Frank; Darwiche, Nadine; Abou Merhi, Raghida (Oncology Reports, 2018)
Primary effusion lymphoma (PEL) is a rare B-cell neoplasm, associated with Kaposi sarcoma-associated herpes virus/human herpes virus-8 (KSHV/HHV-8), arising as malignant effusions in body cavities. PEL cells do not harbor conventional genetic cancer mutations; however, their oncogenesis is mainly attributed to HHV-8 latent genes. Treatment strategies are inefficient resulting in poor prognosis of PEL patients, stressing the need for new effective therapy. ST1926 is a synthetic retinoid with favorable antitumor properties and no cross-resistance with the natural retinoid, all-trans retinoic acid. ST1926 has shown potent apoptotic activities on a variety of solid tumors and hematologic malignancies in in vitro and in vivo models. In the present study we elucidated the antitumor activities and underlying molecular mechanism of ST1926 using in vitro, ex vivo, and in vivo PEL preclinical models. ST1926, at sub-micromolar concentrations, displayed potent antiproliferative effects on PEL cell lines and malignant ascites. Furthermore, ST1926 treatment of PEL cells and ascites resulted in their accumulation in the sub-G1 region, S phase cell cycle arrest, early DNA damage, PARP cleavage and p53 activation including the upregulation of its target genes p21 and Bax. However, ST1926 did not significantly modulate HHV-8 latent viral transcripts. Importantly, ST1926 delayed formation of ascites and enhanced survival of PEL mice. These results highlight the therapeutic potential of ST1926 in combination with drugs that target HHV-8 in PEL patients.
EVALuna2:35290